Radiopharmaceuticals for Treatment of Adrenocortical Carcinoma - Kerstin Michalski; Wiebke Schlötelburg; Philipp E. Hartrampf; Aleksander Kosmala; Andreas K. Buck; Stefanie Hahner; Andreas Schirbel (MDPI AG, 2023)
Adrenocortical carcinoma (ACC) represents a rare tumor entity with limited treatment options and usually rapid tumor progression in case of metastatic disease. As further treatment options are needed and ACC metastases are sensitive to external beam radiation, novel theranostic approaches could complement established therapeutic concepts. Recent developments focus on targeting adrenal cortex-specific enzymes like the theranostic twin [123/131I]IMAZA that shows a good image quality and a promising therapeutic effect in selected patients. But other established molecular targets in nuclear medicine such as the C-X-C motif chemokine receptor 4 (CXCR4) could possibly enhance the therapeutic regimen as well in a subgroup of patients. The aims of this review are to give an overview of innovative radiopharmaceuticals for the treatment of ACC and to present the different molecular targets, as well as to show future perspectives for further developments since a radiopharmaceutical with a broad application range is still warranted.